Enhancing Teacher Competence in Coding Through Gamified Training: A Kirkpatrick Evaluation - Samsuryadi Samsuryadi; Dewi Sartika; Meylani Utari; Kanda Januar Miraswan; Alvi Syahrini Utami; Mgs. Afriyan Firdaus; Osvari Arsalan (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2026)
Background: The Indonesian government, through the Ministry of Primary and Secondary Education (Kemendikdasmen), plans to implement coding and artificial intelligence learning programs in schools starting the 2025/2026 academic year. SMP Negeri 56 Palembang seeks to prepare by enhancing teacher competence in coding, as 56.8% of teachers initially had no basic coding knowledge. Purpose of the Study: This study aims to provide basic coding knowledge to teachers and develop skills in utilizing educational games (Blockly Game Maze) as interactive learning media that can be integrated into the learning process. Methods: Training and workshops were conducted involving 37 teachers from various subjects. A Kirkpatrick model evaluation was applied across four levels: reaction (participant satisfaction), learning (pre-test and post-test comparison), behavior (classroom observation during mentoring), and results (overall program effectiveness). Participants used e-modules and practiced with Blockly Game Maze educational games. Results: The reaction level showed a 94.59% satisfaction rate, indicating high relevance of training materials. The learning level demonstrated a 27.03% increase in coding competency, with participants previously unfamiliar with basic coding (56.8%) beginning to master basic logic and coding structures. At the behavior level, students in five groups successfully completed Blockly Game Maze up to level 6 (100%), with three groups completing level 7. These findings prove that the training not only provided theoretical insights but also successfully built teachers' confidence in adopting new technologies to support the learning process.